Parental Support, Control and Adolescent Religiosity: An Extension of Previous Research - Weigert, Andrew J. (Journal for the scientific study of religion, 1972)
Previous research has found that parental control and support are jointly related to religiosity among urban Catholic adolescents. The present research yielded substantially the same findings among a sample of Mormon adolescents in a small university town in the western United States.